PENGEMBANGAN ALAT EVALUASI PEMBELAJARAN SEJARAH MENGGUNAKAN APLIKASI KAHOOT DENGAN POLA BERPIKIR KRONOLOGIS SISWA PADA MATERI SEJARAH KELAS XI IPS DI SMA NEGERI 1 KOTAGAJAH - Adi Surya Nugraha; Kuswono Kuswono (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
This study aims to produce a learning evaluation tool that is suitable for use in the learning process. This development research uses 5 stages from 10 stages of the Borg and Gall method, namely potential and problems, data collection, product design, design validation, design revision. This research was conducted at SMA Negeri 1 Kotagajah, XI IPS grade students. The instrument used was the eligibility questionnaire by the evaluation expert and the student response questionnaire. The results of the validation study by an evaluation expert obtained a percentage of 95% or in the